Evergreens are green - Canizares, Susan (New York : Scholastic Inc., 1998)
Photographs and simple text explore the contrast between evergreens and delicious trees through the four seasons.
"Scholastic early childhood"--Includes index
Keywords: Trees -- Juvenile literature; Conifer -- Juvenile literature